(untitled) (African Human Mobility Review, 2021)
Informal cross-border trading is an essential part of Maputo’s informal economy. This paper presents the results of a 2014 SAMP survey of informal entrepreneurs involved in cross-border trade between Johannesburg and Maputo. A questionnaire was administered to a sample of 403 informal traders in 7 markets in Maputo. The study showed that most of the entrepreneurs began their business activities as vendors and only later moved into cross-border trading. The overwhelming majority used their personal savings to start their business and they face significant barriers in accessing business loans from formal banking channels. The study demonstrates the importance of cross-border traders to both the Mozambican and South African economy. In South Africa, the cross-border traders make a significant contribution by buying local goods and utilising the services provided by the country’s travel and hospitality industry. In Mozambique, they supply affordable products to the country’s growing informal sector and play an important role in generating employment.